2011
DOI: 10.1517/14712598.2011.554814
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived growth factor applications in periodontal and peri-implant bone regeneration

Abstract: Introduction Achieving successful tissue regeneration following traditional therapeutic protocols, combining bone grafts and barrier membranes, may be challenging in certain clinical scenarios. A deeper understanding of periodontal and peri-implant wound healing and recent advances in the field of tissue engineering have enabled clinicians with novel means to obtain predictable clinical outcomes. The use of growth factors such as recombinant human platelet-derived growth factor-BB (rhPDGF) with biocompatible m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
142
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(152 citation statements)
references
References 34 publications
(30 reference statements)
2
142
0
2
Order By: Relevance
“…To further promote healing and regeneration, MTZ was encapsulated in the outer functional layer at a dosage effective to inhibit periodontopathogen, whereas PDGF was encapsulated in the inner functional layer to promote mitogenesis. 11,[14][15][16] The sustained release of MTZ and PDGF ( Figure 1E) inhibited of biofilm formation 23 and enhanced the chemotaxis of MSCs, 24 suggesting that FGM may exert beneficial effects in vivo. …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…To further promote healing and regeneration, MTZ was encapsulated in the outer functional layer at a dosage effective to inhibit periodontopathogen, whereas PDGF was encapsulated in the inner functional layer to promote mitogenesis. 11,[14][15][16] The sustained release of MTZ and PDGF ( Figure 1E) inhibited of biofilm formation 23 and enhanced the chemotaxis of MSCs, 24 suggesting that FGM may exert beneficial effects in vivo. …”
Section: Discussionmentioning
confidence: 97%
“…MTZ is an antibiotic specific to the Gram-negative anaerobic bacteria 11 and is widely used to support dentoalveolar regeneration. 10,12,13 In addition, we incorporated platelet-derived growth factor (PDGF), a potent mitogen and chemoattractant, 14 in the nanofibers on the inner surface to facilitate the healing and regeneration process. We assessed the biocompatibility and applicability of this FGM design in a cell-based system and in rodent models.…”
mentioning
confidence: 99%
“…Recent studies have suggested that a number of growth factors, including PDGF, promote tissue repair and regeneration, including bone formation; moreover, the efficacy of growth factor therapies in periodontology and implantology has been well characterized in a variety of in vitro and in vivo studies (7,8). The present study, focused on the histological characteristics of the early osseointegration of implants, with or without addition of PRP and PDGF/IGF-1 in combination, in an animal model, demonstrate a higher bone regeneration rate in growth factors-treated group than in PRP or control group.…”
Section: Discussionmentioning
confidence: 99%
“…The process of remodeling is slowed down from the 12 th to the 16 th week and the PDGF-level gradually declines 14 . This growth factor has been isolated, and nowadays it is recommended in the treatment of bone defects as highly purified recombinant human rh PDGF-BB 15 .…”
Section: Transformacioni Faktor Rasta Tgf-βmentioning
confidence: 99%